Faith, Works and Grace According to Saint Augustine and Its Pedagogical Relevance - Alexandre Rodrigues Gomes (Ignatianum University Press, 2022)
This article deals with the concept of Saint Augustine about faith, works and grace, showing, according to his philosophical and theological perspective, what would be the faith worthy of being considered true and what would be, therefore, a false faith. Regarding divine grace, it is discuted here the controversy between Augustine and Pelagius, which shook the Church in middle of the 5th century. The text reflects to what extent and in what way Saint Augustine's thought is still relevant for current times, both for Christians and non-Christians. Finally, the article speculates on how Augustinian approaches on the aforementioned issues are relevant for education and moral formation of individual.   Este artículo versa sobre el concepto de san Agustín acerca de la fe, las obras y la gracia, mostrando, según su perspectiva filosófica y teológica, cuál sería la fe digna de ser considerada verdadera y cuál sería, por consiguiente, una fe falsa. Por lo que respecta a la gracia divina, el texto discute la polémica entre Agustín y Pelagio, que sacudió a la Iglesia a mediados del siglo V. Igualmente, expone en qué medida y de qué manera el pensamiento de san Agustín sigue siendo relevante para los tiempos actuales, tanto para cristianos como para no cristianos. Finalmente, el artículo analiza de qué modo los planteamientos agustinianos sobre los temas arriba mencionados son relevantes para la educación y la formación moral del individuo.